Simultaneous Determination of Nirmatrelvir and Ritonavir in Human Plasma by HPLC-MS/MS - T. N. Komarov; P. K. Karnakova; O. A. Archakova; D. S. Shchelgacheva; N. S. Bagaeva; I. E. Shohin; K. Ya. Zaslavskaya; P. A. Bely (Разработка и регистрация лекарственных средств, 2023)
Introduction. SARS-CoV-2 (severe acute respiratory syndrome-related coronavirus 2) is expected to remain a persistent global threat. Therefore, development of coronavirus disease 2019 (COVID-19) drugs is the most urgent global issue. Nirmatrelvir and ritonavir combination is an oral antiviral drug combination with activity against SARS-CoV-2. Nirmatrelvir and ritonavir combination is highly efficacious in reducing the risk of COVID-19. The study describes development and validation of high-performance liquid chromatography – tandem mass spectrometry (HPLC-MS/MS) method for the simultaneous determination of nirmatrelvir and ritonavir in human blood plasma. The method could be applied in pharmacokinetic study of nirmatrelvir and ritonavir.Aim. The aim of this study is to develop and validate a HPLC-MS/MS bioanalytical method for the determination of nirmatrelvir and ritonavir in human plasma.Materials and methods. The determination of nirmatrelvir and ritonavir in human plasma by HPLC-MS/MS. The samples were processed by acetonitrile protein precipitation. Internal standard: promethazine. Mobile phase: 0.1% formic acid solution in water (Eluent A), 0.1% formic acid in acetonitrile (Eluent B). Column: Phenomenex Luna C18 50 × 2.0 mm, 5 μm. Analytical range: 50.00–10000.00 ng/mL for nirmatrelvir, 5.00–1000.00 ng/mL for ritonavir in human plasma. Ionization source and ionization: electrospray ionization, positive. Detection conditions: 499.90 → 110.10 m/z, 499.90 → 319.20 m/z (nirmatrelvir), 720.90 → 426.00 m/z, 720.90 → 296.20 m/z, 720.90 → 268.10 m/z, 720.90 → 197.10 m/z, 720.90 → 139.90 m/z (ritonavir), 285.15 → 198.05 m/z (promethazine).Results and discussion. This method was validated for selectivity, matrix effect, calibration curve, accuracy, precision, spike recovery, the lower limit of quantification, carry-over effect and stability.Conclusion. The HPLC-MS/MS method for quantitative determination of nirmatrelvir and ritonavir in human plasma was developed and validated. The analytical range was 50.00–10000.00 ng/mL for nirmatrelvir, 5.00–1000.00 ng/mL for ritonavir in human plasma. This method was applied to investigate the pharmacokinetics of nirmatrelvir and ritonavir.